2015
DOI: 10.1124/mol.114.097220
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into Metabotropic Glutamate Receptor Allosteric Modulation

Abstract: The metabotropic glutamate (mGlu) receptors are a group of eight family C G protein-coupled receptors that are expressed throughout the central nervous system (CNS) and periphery. Within the CNS the different subtypes are found in neurons, both pre-and/or postsynaptically, where they mediate modulatory roles and in glial cells. The mGlu receptor family provides attractive targets for numerous psychiatric and neurologic disorders, with the majority of discovery programs focused on targeting allosteric sites, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 149 publications
(218 reference statements)
3
31
0
Order By: Relevance
“…In both crystal structures, the allosteric ligand‐binding pocket is extracellularly accessible and resides between TM2, TM3, TM5, TM6 and TM7 (Dore et al ., ; Wu et al ., ). This pocket is consistent with extensive previous mutagenesis studies of the ‘2‐methyl‐6‐(phenylethynyl)pyridine (MPEP) binding site’ or the common allosteric site that is shared across multiple mGlu 5 receptor allosteric modulator chemotypes, including NAMs, PAMs and NALs (Gregory and Conn, ). Indeed, the crystal structures are also consistent with structure‐function studies of allosteric pockets across multiple family C GPCRs (Bennett et al ., ; Gregory and Conn, ), suggesting a common location for binding cavities in family C GPCRs that can be selectively targeted with small molecule allosteric ligands.…”
Section: Location Of Mglu5 Allosteric Binding Sitessupporting
confidence: 89%
See 1 more Smart Citation
“…In both crystal structures, the allosteric ligand‐binding pocket is extracellularly accessible and resides between TM2, TM3, TM5, TM6 and TM7 (Dore et al ., ; Wu et al ., ). This pocket is consistent with extensive previous mutagenesis studies of the ‘2‐methyl‐6‐(phenylethynyl)pyridine (MPEP) binding site’ or the common allosteric site that is shared across multiple mGlu 5 receptor allosteric modulator chemotypes, including NAMs, PAMs and NALs (Gregory and Conn, ). Indeed, the crystal structures are also consistent with structure‐function studies of allosteric pockets across multiple family C GPCRs (Bennett et al ., ; Gregory and Conn, ), suggesting a common location for binding cavities in family C GPCRs that can be selectively targeted with small molecule allosteric ligands.…”
Section: Location Of Mglu5 Allosteric Binding Sitessupporting
confidence: 89%
“…This pocket is consistent with extensive previous mutagenesis studies of the ‘2‐methyl‐6‐(phenylethynyl)pyridine (MPEP) binding site’ or the common allosteric site that is shared across multiple mGlu 5 receptor allosteric modulator chemotypes, including NAMs, PAMs and NALs (Gregory and Conn, ). Indeed, the crystal structures are also consistent with structure‐function studies of allosteric pockets across multiple family C GPCRs (Bennett et al ., ; Gregory and Conn, ), suggesting a common location for binding cavities in family C GPCRs that can be selectively targeted with small molecule allosteric ligands. Commensurate with this concept is the fact that some mGlu 5 receptor allosteric ligands have activity at other mGlu subtypes (Mathiesen et al ., ; O'Brien et al ., ; Sheffler et al ., ).…”
Section: Location Of Mglu5 Allosteric Binding Sitessupporting
confidence: 89%
“…In particular, allosteric modulation of the mGlu 5 receptor has been of interest as a target for the treatment of schizophrenia and Alzheimer disease (65,66). As such, multiple small molecule PAMs have been developed for mGlu 5 (67)(68)(69)(70)(71)(72), with the bulk acting at a common site in the upper region of the 7TM domain often termed the "MPEP-binding site" after the prototypical mGlu 5 NAM, MPEP (65,66). However, several ligands have been identified that are non-competitive with the MPEP site, including the PAMs VU357121 and CPPHA, indicating the presence of at least two distinct allosteric sites (67,69,73,74).…”
Section: Exogenous Allosteric Modulatorsmentioning
confidence: 99%
“…Given the vast number of possible allosteric binding sites there is reason to believe that many of these sites have not been identified or targeted from a medicinal chemistry perspective. Numerous examples have been detailed where multiple distinct allosteric binding sites have been found for a single GPCR subtype (Gregory and Conn, 2015), and the recent discovery of a cytoplasmic allosteric binding site in chemokine CCR9 represents one example of a previously unappreciated binding site that could allow therapeutic modulation of a previously intractable target (Oswald et al, 2016). As we continue to advance our understanding of the mechanisms underlying allosteric modulation of GPCRs, we have come to appreciate the immense number of conformations and higher-order complexes that these receptors can adopt (Changeux and Christopoulos, 2016; Latorraca et al, 2016), and are beginning to elucidate how these conformations differentially regulate various signaling pathways.…”
Section: Discussionmentioning
confidence: 99%